2015
DOI: 10.5465/ambpp.2015.14282abstract
|View full text |Cite
|
Sign up to set email alerts
|

Resource Orchestration as a Source of a Competitive Advantage for Cities

Abstract: -DeutschInmitten des aktuellen Urbanisierungstrends bietet diese Dissertation eine Antwort auf den Mere resources are frequently insufficient to generate competitiveness in our increasingly demanding world; urban administrators, policymakers and other practitioners concerned with the management of their place need capabilities to use resources efficiently while adapting to their changing environments. Therefore, I argue for the value of extending the resource-based theory -especially, its dynamic refinement, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…Competitive advantage rests to a large extent on the capabilities of the HEIs to sense opportunities for accessing and seizing new resources, and then reconfiguring them internally. Berseck and Zu Knyphausen-Aufseß (2018) and Muneeb et al (2020), suggested that higher education policymakers need capabilities to use and recombine resources efficiently while simultaneously adapting to their changing environments for HEI competitiveness. It can be argued that DCs are instrumental in determining the capacity of a firm to successfully implement actions that result in a sustained competitive advantage (Hou and Chien, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Competitive advantage rests to a large extent on the capabilities of the HEIs to sense opportunities for accessing and seizing new resources, and then reconfiguring them internally. Berseck and Zu Knyphausen-Aufseß (2018) and Muneeb et al (2020), suggested that higher education policymakers need capabilities to use and recombine resources efficiently while simultaneously adapting to their changing environments for HEI competitiveness. It can be argued that DCs are instrumental in determining the capacity of a firm to successfully implement actions that result in a sustained competitive advantage (Hou and Chien, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Small firms operating in DCs are often challenged by a lack of resources to further their development; hence, EO could enable them to overcome the limitations and weakness of formal institutional environments in DCs to access needed resources and use them. Firm owners/entrepreneurs who want to orchestrate their resources and strengthen their firm's resilience in this context must develop EO capabilities across various organizational boundaries (Berseck and zu Knyphausen-Aufseß 2018). Social networking is also a valuable strategy that entrepreneurs need to consider, in combination with EO, especially for resource acquisition in the DC context.…”
Section: For Entrepreneursmentioning
confidence: 99%